An efficient melting probe for glacial research. Issue 84 (15th April 2021) - Heinen, Dirk; Linder, Peter; Zierke, Simon; Wiebusch, Christopher
Abstract: In this paper, we present an electric-thermal drill with a novel design of a melting head that was developed within the EnEx-RANGE project. The design combines a short melting head with a large surface area of parabolic shape. It was succesfully tested in the laboratory as well as on Alpine glaciers (Langenferner and Mittelbergferner) and at the Ross Ice Shelf in Antarctica. In all these different environments, a high melting speed per specific power of typically 8.8 cm 3 w −1 h −1 is achieved that is close to the ideal maximum bound of 10.5–11.8 cm 3 w −1 h −1 when neglecting all heat losses. It has also been demonstrated that the melting probe can be operated with typical equipment of small-scale field camps including a small power generator.